Age-Dependent Changes in the Function of Mitochondrial Membrane Permeability Transition Pore in Rat Liver Mitochondria - Endlicher, R; Drahota, Z; Kučera, O; Červinková, Z (Physiological research, 2021)
Mitochondria play an important role in the cell aging process. Changes in calcium homeostasis and/or increased reactive oxygen species (ROS) production lead to the opening of mitochondrial permeability transition pore (MPTP), depolarization of the inner mitochondrial membrane, and decrease of ATP production. Our work aimed to monitor age-related changes in the Ca2+ ion effect on MPTP and the ability of isolated rat liver mitochondria to accumulate calcium. The mitochondrial calcium retention capacity (CRC) was found to be significantly affected by the age of rats. Measurement of CRC values of the rat liver mitochondria showed two periods when 3 to 17-week old rats were tested. 3-week and 17-week old rats showed lower CRC values than 7-week old animals. Similar changes were observed while testing calcium-induced swelling of rat liver mitochondria. These findings indicate that the mitochondrial energy production system is more resistant to calcium-induced MPTP opening accompanied by the damaging effect of ROS in adult rats than in young and aged animals.
Keywords: Aging; jaterní mitochondrie; krysa rodu Rattus; Animals; Mitochondria, Liver; mužské pohlaví; zvířata; potkani Wistar; Male; Rats, Wistar; Rats; stárnutí; přechodový pór mitochondriální permeability; Mitochondrial Permeability Transition Pore